2013
DOI: 10.1007/s00125-013-2848-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of induced hyperinsulinaemia with and without hyperglycaemia on measures of cardiac vagal control

Abstract: Aims/hypothesis We examined the effects of serum insulin levels on vagal control over the heart and tested the hypothesis that higher fasting insulin levels are associated with lower vagal control. We also examined whether experimentally induced increases in insulin by beta cell secretagogues, including glucagon-like peptide-1 (GLP-1), will decrease vagal control. Methods Respiration and ECGs were recorded for 130 healthy participants undergoing clamps. Three variables of cardiac vagal effects (the root mean s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 35 publications
3
24
2
Order By: Relevance
“…The observed HR acceleration of 4.3 beats min −1 is consistent with previous acute GLP‐1(RA) infusion studies, with effects ranging from no effect , to increases of up to 8.2 beats min –1 . With long term treatment, a mean HR acceleration of 2 beats min –1 is commonly observed in type 2 diabetes patients, but can be as high as ~10 beats min –1 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The observed HR acceleration of 4.3 beats min −1 is consistent with previous acute GLP‐1(RA) infusion studies, with effects ranging from no effect , to increases of up to 8.2 beats min –1 . With long term treatment, a mean HR acceleration of 2 beats min –1 is commonly observed in type 2 diabetes patients, but can be as high as ~10 beats min –1 .…”
Section: Discussionsupporting
confidence: 88%
“…Notably, in other studies using exogenous GLP‐1 peptide vs . placebo, HR increased during clamped hyperglycaemia (10 mmol l −1 ) . Moreover, after meal ingestion, HR increased with GLP‐1 infusion despite increases in blood glucose .…”
Section: Discussionmentioning
confidence: 90%
“…Previous research in adults showed a positive correlation of glucose intake, plasma insulin levels and functional changes in the ANS. As blood levels of glucose and insulin rose, mean heart rate increased . This is thought to be related to a concomitant sympathetic activation …”
Section: Discussionmentioning
confidence: 85%
“…Recent studies [51,52] have shown that increased insulin and leptin levels are known to adversely affect autonomic nervous system function. High levels of leptin have been shown to be associated with decreased cardiac tone, and hyperinsulinemia to be associated with lower levels of heart rate variability [53,54].…”
Section: Discussionmentioning
confidence: 99%